Pengaruh Pendidikan Kesehatan Gigi Terhadap Pengetahuan dan Sikap Anak Usia Sekolah di SD Boto Kembang Kulonprogo Yogyakarta - Isrofah .; Nonik Eka M (Universitas Pekalongan, 2010)
Teeth health education for school age is very important because that period is critics’ age or teeth development and also for psychology development so need approach method to knowledge and attitude especially oral and teeth health. So that teeth health education is done in Boto Kembang Elementary School Nanggulan Kulon Progo Yogyakarta. This Research’s have aim is to know health education effect about oral and teeth health to the knowledge and attitude in oral and teeth health care. The research is pre experimental research by One Group Pretest Posttest Design. Respondent in this research are all the students in class 3 and 4 in Boto Kembang Elementary School about 8 – 12th years old, they are 30 students and taking the sample with total sampling technique. Research instrument is questioner. The statistical test is making use of SPSS with the level significant p<0, 05. Knowledge and attitude analysis in school age in Boto Kembang Elementary School show that before given education, the knowledge level is good, 9 respondents and after given health education, 27 respondents are good. Data analyses for attitude, before given health education, respondent with good attitude level are 26 respondents and after given healtheducation become 26 respondents. T-test result show -0, 969, means that health education about teeth not affect the knowledge for school age. The conclusion of this research is that oral and teeth health education effect the knowledge but do not effect to the attitude school age about oral and teeth health care.Keywords: Teeth health education, knowledge, Attitude.